Análise sísmica não linear de igreja edificada no século VXIII em alvenaria vernacular - Pinto, Marcelo Freires (2019)
The applicability of investigative computational approaches allows simulating for unconventional structural mechanisms of the historical heritage, where the conversion of requests into mechanisms detrimental to safety and performance parameters is closely related to historical, cultural and economic factors. Addressing the development of activities of this nature is still a challenge, considering the limitations of technical data regarding the high divergence of construction methods and investigative procedures subject to the requirements of this group of buildings. In this sense, it is necessary to be aware of the value of these assets as a common heritage to last in future generations, as well as to promote and publicize actions that may be associated with tools for the protection. Therefore, the present work aims to analyze, under nonlinear simulations in static regime, the global behavior of a building in vernacular masonry of the eighteenth century, the Church Nossa Senhora do Rosário dos Pretos. To this end, a three-dimensional model of the building was constructed using the Finite Element Method (FEM) to carry out a modal analysis in elastic regime. After that, the identification of weaknesses allowed the creation of two additional numerical models of equivalent gantries in bar elements. nonlinear pushover seismic analysis for requests on the longitudinal and transverse axes of the building. The results in elastic regime indicated two vibration modes with mass participation predominantly for each of the analyzed axes, followed by bell tower requests for the two axes with the second amount of effective mass among the ten extracted modes. Therefore, the modal analysis validated the interest in the construction of bell tower models for the elaboration of resistant capacity curves, while the nonlinear analysis identified the first requested region in the longitudinal axis, in modal analysis, as a critical region , with target displacement up to 0,134 meters in a plastic scenario that begins with 0,42 meters deformations . These results provided valuable information to assist in actions that require technical decisions, assigning numerical simulations, the form of an investigative instrument that can be aligned with the safety and durability assumptions required in heritage buildings.